Merger and acquisitions - Coyle, Brian (United Kingdom: CIB Publishing, 2000)
This is a guide to the reasons why and processes by which one company may be bought by another or merge with a competitor. It presents a broad analysis of mergers and acquisition strategies and describes the takeover process, including valuations and structuring a deal.
Glossary p. 117
Includes index.
osa 5/9/16, rpm 09/09/16
Loans
Keywords: Merger and acquisition; Consolidation and merger of corporations; Corporate reorganizations